A prospective, single-centered, cohort study comparing the treatment of renal stones by following PCNL types: Standard, tubeless & totally tubeless. (August 2022) - Ahmad, Mumtaz; Mumtaz, Hassan; Hussain, Hassan ul; Sarfraz, Sharjeel; Rahat, Manahil; Mumtaz, Shamim
Abstract: Introduction: Renal stones are a frequent cause of morbidity globally. The number of lumbotomies performed for benign lithiasis has been greatly decreased with the usage of Percutaneous Nephrolithotomy (PCNL). Further development is aimed at reducing tract size, leading to numerous advanced minimally invasive PCNL procedures like mini-PERC, ultra-mini-PERC, and micro-PERC. The aim of this study was to evaluate whether tubeless or totally tubeless PCNL is the safest and most efficient, less morbid management technique for renal stones compared to the standard PCNL with a nephrostomy tube. Methodology: This is a comparative, prospective, single-centered, cohort study that took place between August 2015 and January 2018 in the Urology department of Benazir Bhutto Hospital in Rawalpindi, Pakistan. 218 patients having single/multiple stones of variable sizes were enrolled in the study. Participants were stratified into three groups; Group A: Standard PCNL treatment; Group B: Tubeless PCNL treatment; Group C Totally Tubeless treatment. Mean operation time (±SD) and stone-free rates were our primary outcomes. The rate of complications during and post-operative complications were our secondary outcomes. Results: A total of 181 patients were included in our study. A decreasing trend can be seen in mean operation time as we move from Group A to Group C (p  =  0.000) . The rate of problems during operation in each group was highest (45.8%) in Group A, much lesser problems in Group C (13.3%), and least problems in Group B (8.1%) (p  =  0.000) . The postoperative complication rate was again the highest in Group A (30.5%), low in Group C (8.3%), and extremely low in Group B (1.6%) Conclusion: Tubeless PCNL proved to be the safest and most effective when compared to standard and totally tubeless PCNL procedures. It also showed the highest stone-free rates and least 'unsatisfactory' results amongst all the groups. Conclusively, it should be performed in routine preferably. Highlights: In terms of safety and efficacy, tubeless PCNL outperformed both regular and completely tubeless PCNL. The Tubeless PCNL is much superior than other techniques of PCNL. Aftercare and difficulties during surgery are virtually nonexistent with tubeless PCNL. Stone-free rates were also the highest and the least "unsatisfactory" across all groups. Finally, it's best if it's done on a regular basis.